THERMAL COMFORT AND PRODUCTIVITY OF PIGS - Gyria, V. M.; Usachova, V. Ye.; Myronenko, O. I.; Slynko, V. G. (Scientific Progress & Innovations, 2019)
A modern notion of the temperature factor significance for the well-being of pigs and measures aimed at reducing the negative impact of the climate change and solving related problems are presented. The effect of climate change on pigs’ productivity, the justification of adapting and preventing the possibility of temperature stress were analyzed. The reaction of pig organism on violating thermal comfort was disclosed. The unsatisfactory state of livestock premises’ microclimate negatively affects the viability of the animal organism, heat overstrain is observed accompanied by deteriorating appetite and feed consumption, as well as the resistance of animals to pathogens, parasites. The numerous factors of stress seriously affect manufacturing livestock products, reproduction, immune status and production effectiveness in general. The mechanisms of heat regulation in the animal organism at temperature stress and its negative influence on pig productivity indices of different production groups were considered. The data as to the measures of pig adaptation to environmental conditions in the premises, which can help to solve their adaptation in the conditions of thermal stress and can be minimized by controlling the temperature in the premises, ventilating, heating and cooling systems, spraying water were poresented. The main directions of the strategy of pig heat resistance control connected with using of different breeding programs, new stress biomarkers, innovative rearing technologies were outlined. A separate role was specified as to using more saturated feed rations with a reduced level of crude protein and fiber in the diet, as well as adjusting the supply of feed portions. The given information can be used in scientific researches, introduced into production, educational process in training specialists in the field of technology of manufacturing livestock farming products.